Evaluation of human anatomy in emergency remote teaching - García Barrios, Alberto; Cisneros Gimeno, Ana Isabel; Lamiquiz Moneo, Itziar; Whyte Orozco, Jaime (Spanish Journal of Medical Education, 2021)
The objective of the study was twofold: to evaluate student satisfaction with the online assessment, and the differences in this assessment according to whether it was carried out at home or in the classroom. The design and methodology were based on satisfaction surveys of the type of evaluation and a statistical analysis to assess the differences in the results according to the place where the evaluation was carried out. The students' evaluation does not show unanimity (53%) in considering online evaluation as a good evaluation method, although 67% and 90% (depending on the course and subject) would use digital tools to evaluate face-to-face. The reduction of time and connection are the main disadvantages valued. The results of the global evaluation do not show changes depending on whether it is face-to-face or distance. Therefore, we consider that the use of new technologies for evaluation has been well accepted by students and teachers, and no different results are observed for face-to-face or distance learning.